1984
DOI: 10.1128/aac.26.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of amikacin concentrations in perilymph and plasma of continuously infused guinea pigs

Abstract: A commercially available radioimmunoassay kit was modified to enable us to measure, in triplicate, the amikacin concentration in 1 ,ld of perilymph fluid. Amikacin levels in plasma and perilymph were measured in guinea pigs after continuous intravenous infusion at four different dosing rates. After a 4-h infusion, a good linear correlation was found between the amikacin concentration in plasma and the dosing rate. Likewise, a significant linear relationship was found between concentrations of amikacin In peril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This dose was derived from the perilymph-to-serum aminoglycoside ratio of 20% after a 6-hour i.v. infusion9, and likely higher than GTTR levels in perilymph 30 minutes after systemic injection7. After 30 minutes, there was negligible GTTR fluorescence in the stria vascularis and weak fluorescence in hair cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This dose was derived from the perilymph-to-serum aminoglycoside ratio of 20% after a 6-hour i.v. infusion9, and likely higher than GTTR levels in perilymph 30 minutes after systemic injection7. After 30 minutes, there was negligible GTTR fluorescence in the stria vascularis and weak fluorescence in hair cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We assumed that the concentration of amikacin would increase at the same rate and would therefore reach the same level after infusion for 6 h in both ears since previous studies (4,5) found no statistical difference between the amikacin concentrations of both ears. Although blood contamination during perilymph sampling cannot be completely discounted as a possible cause for the higher concentration of amikacin measured in the multiply sampled ear, it is unlikely to be an important factor since minor blood contamination of the perilymph would have been easily observed.…”
mentioning
confidence: 99%
“…Since the perilymph compartment is both small and poorly accessible, generally only a single data point can be obtained from each animal (3,15). We recently modified a radioimmunoassay technique so that only 1 ,ul of perilymph sample is required (4). This small size made multiple sampling of the perilymph feasible in an anesthetized animal.…”
mentioning
confidence: 99%
See 2 more Smart Citations